Implementasi Program Ecobrick dalam Pembuatan Plang Nama Timbulun Tujuh Nagari Sibakur Kabupaten Sijunjung - Pulungan, Ali Basrah; Saputra, Irwan; Yosefani, Fiveva Tria Chantika; Sania, Putri; Andrina, Alisya; Amiyatno, Rifki (Yayasan Daarul Huda Kruengmane, 2025)
This article describes the implementation of the Ecobrick program in creating the nameplate “Timbulun Tujuh” located in Nagari Sibakur, Tanjung Gadang District, Sijunjung Regency. This program is part of the community service activity of Universitas Negeri Padang students through the Community Service Program (KKN), focusing on plastic waste management and environmental preservation. The main purpose is to transform plastic waste into environmentally friendly constructive materials with practical value, while at the same time promoting local identity through visual media. The methods applied include community socialization, plastic waste collection, ecobrick production, as well as the design and installation of the nameplate. Data were collected through direct observation, interviews with local residents and village officials, and documentation during the process. The results show that the community, especially the younger generation, became more aware of the importance of plastic recycling and actively participated in the ecobrick and nameplate-making process. Beyond producing a functional and artistic nameplate, this activity also raised environmental awareness and strengthened local identity in Nagari Sibakur. The program implies the need for similar initiatives to be continued on a wider scale as part of community-based environmental education.